Strategic Taxpayer Compliance During the Covid-19 Pandemic: A Study at the Medan Two Intermediate Tax Service Offices - Najamuddin, Najamuddin; Muktiyanto, Ali; Asnawi, Said Kelana (Pusat Studi Pembangunan dan Pemberdayaan, 2024)
This study aims to analyze strategic taxpayer compliance during the Covid-19 pandemic at the Medan Madya Dua Tax Office using quantitative methods. The research population is 1,966 taxpayers, consisting of 1,800 corporate taxpayers and 166 individual taxpayers. Independent variables include tax incentives, tax counseling, tax sanctions, supervision by Account Representative (AR), and tax audits, while the dependent variable is taxpayer compliance. Data were measured using dummy variables and nominal scales, and analyzed by multinomial logistic regression. The results showed that tax sanctions with a fine category of more than 2,000,000 tended to make taxpayers report tax returns on time with a probability of 59.63% higher than those on time. AR supervision with the SP2DK issuance category also increases the probability of late SPT reporting by 59.23%. The study shows that the variables of incentives, counseling, sanctions, AR supervision, and tax audits significantly affect taxpayer compliance in reporting annual tax returns. It is recommended that further research be carried out at the Primary and post-pandemic Tax Service Offices.